2019
DOI: 10.3389/fnins.2019.00145
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Global-Brain Functional Connectivity in the Left Superior Frontal Gyrus as a Possible Endophenotype for Schizophrenia

Abstract: The notion of dysconnectivity in schizophrenia has been put forward for many years and results in substantial attempts to explore altered functional connectivity (FC) within different networks with inconsistent results. Clinical, demographical, and methodological heterogeneity may contribute to the inconsistency. Forty-four patients with first-episode, drug-naive schizophrenia, 42 unaffected siblings of schizophrenia patients and 44 healthy controls took part in this study. Global-brain FC (GFC) was employed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 93 publications
0
20
0
Order By: Relevance
“…Hanford et al 29 suggest this could reflect operation of compensatory processes in higher-performing SZH. Furthermore, enhanced functional connectivity of the left superior frontal gyrus has been put forward as a potential phenotypic marker for the disease: Ding et al 64 found increased functional connectivity specific to the left superior frontal gyrus in both drug-naive SZH and their unaffected siblings; connectivity values of this region could differentiate patients and siblings from controls with good sensitivity, and values did not correlate with symptom severity or illness duration suggesting it could represent a trait marker. However, Ding et al 64 did not assess links with cognition; the current findings suggest this is an important avenue to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Hanford et al 29 suggest this could reflect operation of compensatory processes in higher-performing SZH. Furthermore, enhanced functional connectivity of the left superior frontal gyrus has been put forward as a potential phenotypic marker for the disease: Ding et al 64 found increased functional connectivity specific to the left superior frontal gyrus in both drug-naive SZH and their unaffected siblings; connectivity values of this region could differentiate patients and siblings from controls with good sensitivity, and values did not correlate with symptom severity or illness duration suggesting it could represent a trait marker. However, Ding et al 64 did not assess links with cognition; the current findings suggest this is an important avenue to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, FC based on the assumptive network of interest may lead to biased results and limits the investigation of the most remarkably altered brain areas that may represent the essential abnormality in the neurobiological mechanisms of OCD (19). Voxel-wise global brain FC (GFC) analysis is a model-free method used to investigate functional interactions across the whole brain regions with an unbiased hypothesis-driven manner, and has been applied to obtain whole brain FC in patients with major depressive disorder (19), schizophrenia (20), and somatization disorder (21).…”
Section: Introductionmentioning
confidence: 99%
“…The GFC method used in the study is similar to that used in our previous studies (Cui et al, 2018 , 2020 ; Ding et al, 2019 ; Pan et al, 2019a , b ; Li et al, 2020 ). GFC is a measure of functional connectivity of all voxels in the brain with respect to other voxels.…”
Section: Methodsmentioning
confidence: 99%